Optical properties of compounds with submicron points obtained through Ga2S3 intercalation with Cd [Articol] - Racoveț, O.; Evtodiev, I.; Caraman, Iu.; Rotaru, I.; Lazăr, G. (Universitatea de Stat „Alecu Russo“ din Bălţi, 2012)
Luminescence and optical absorption spectra of Ga2S3 single crystals were investigated at temperatures of 78 K and 293 K. Optical band gap is equal to 3.27 eV and 3.457 eV at 293 K and 78 K respectively. Luminescence spectrum of single crystal lamellas at temperature of 78K consists of three bands with peaks at 2.04 eV, 1.84 eV and 1.66 eV.Native structural defects form deep recombination and electronic capture levels localized within the Ga2S3 band gap.

Au fost obţinute spectrele de luminiscenţă şi absorbţie ale monocristalelor Ga2S3 la temperaturi de 78 K şi 293 K. Banda optică interzisă are mărimea de 3,27 eV la 293K şi 3,457 eV la 78 K. Spectrul de luminescenţă al peliculelor monocristaluluipentru temperatura de 78 K este format din trei benzi cu valorile maxime de 2.04 eV,1.84 eV şi 1.66 eV. Defectele structurale proprii iniţiază formarea nivelelor de recombinare şi captare de electroni, localizate în interiorul benzii interzise.
Keywords: Ga2S3; single crystals; intercalation; photoluminescence; absorption; monocristale; intercalare; fotoluminescenţă; absorbţie